Insight into the effect of bromine on facet-dependent surface oxygen vacancies construction and stabilization of Bi2MoO6 for efficient photocatalytic NO removal - Wang, Shengyao; Ding, Xing; Yang, Nan; Zhan, Guangming; Zhang, Xuehao; Dong, Guohui; Zhang, Lizhi; Chen, Hao (Applied catalysis. B, Environmental, 2020)
Benefiting from the Br− selectively induced the OVs on {001} facets of Bi2MoO6, an extended light-absorption until near-infrared region and enhanced the molecular oxygen activation were achieved, thus endowing the OVs concentration optimized Bi2MoO6 with superior activity and selectivity of NO removal in a flow reaction. [Display omitted] •Br− boost the construction and stabilization of OVs on {001} facets of Bi2MoO6.•Br− induced OVs facilitate NO removal of BMO-001-Br even in near-infrared region.•NO oxidative removal with high selectivity of 93.6% is achieved on BMO-001-Br.•Mechanism for highly efficient NO removal (62.9%) over BMO-001-Br is proposed. Surface oxygen vacancies (OVs) are believed as active sites for photocatalytic NO removal. The construction and stabilization of OVs on materials, especially from the point of view of exogenous ions towards different facets is vital for OVs-mediated photocatalysis. Herein, the impact of bromide ions (Br−) on OVs construction on different facets of Bi2MoO6 was systematically investigated. Theoretical calculations and characterizations demonstrated that Br− can boost and stabilize the OVs on {001} facets of Bi2MoO6, while hardly affect that on {010} facets. The Br- induced OVs on Bi2MoO6 caused a light-absorption until near-infrared region and enhanced the molecular oxygen activation, thus endowing the OVs concentration optimized Bi2MoO6 (BMO-001-Br) with superior activity on NO removal (62.9%) and selectivity of NO complete oxidation (93.61%) in a flow reaction. This work provides new insight into understanding the exogenous ions on construction and stabilization of OVs and the roles of OVs in photocatalytic NO removal.